Fast track: fasting replacement recommender mobile application using rule-based / Nurfarah Ain Ahmad Zahid - Ahmad Zahid, Nurfarah Ain (Faculty of Computer and Mathematical Sciences, 2015)
Fasting during the month of Ramadan is obligatory to all the Muslim. However, menstruating women are forbidden to fast during Ramadan. This reason causes the Muslim female necessary to do the fasting replacement later in the year. However, if they are not able to finish their fasting replacement within the specified timeframe, Fidyah will be charged. Based on survey upon Muslimah, it was found 84% of the Muslimah tend to delay fasting replacement and forget to replace it until the coming Ramadan. Therefore, the focus of this project is to develop a mobile application for fasting replacement recommendation. The project aim is to give suggestion day for the user to do fasting replacement. With the rapid growth of smart phone technology nowadays, it is necessary to have this kind of mobile application to remind the user about fasting replacement. The mobile application for fasting replacement recommendation may be able to help user to remember about how many days the user are not fasting during Ramadan as well as it will help user to organize the fasting replacement days. To develop this mobile application, ruled-based technique is used. The suggestion day based on the rules obtained from an expert. In this project, an adapted Mobile Application Development Lifecycle (MADLC) have been utilized. Findings for this project was getting from the survey that have been conducted to random number of menstruating women and an interview have done with an expert. From the survey, it shows that 95% of respondents agreed to have fasting replacement recommendation application. From the survey, 84 percent of respondents tend to forget about fast replacement. As a conclusion, the project’s objectives are achieved and there are some recommendations to improve the project.